Risk factors for recurrence and bleeding in colorectal cancer patients with cancer-associated venous thrombembolism - Liang, Zhikun; Mao, Jieling; Xie, Jingwen; Li, Xiaoyan; Qin, Li (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) patients with cancer-associated venous thromboembolism (VTE) face high risks of recurrence and anticoagulant-related bleeding.ObjectivesOur aim was to assess risk factors associated with recurrence and bleeding and analyze the impact of these outcomes on survival during one-year follow up.DesignRetrospective study.MethodsThis analysis included consecutive VTE patients treated with anticoagulants from January 2019 to January 2023. The incidence of recurrent VTE, major bleeding (MB), and clinically relevant non-major bleeding (CRNMB) was evaluated and their associated risk factors were identified using univariate and multivariate models. Furthermore, the impact of anticoagulant treatment outcomes on all-cause mortality was analyzed by Cox proportional hazards model and Kaplan-Meier method.ResultsThis study included 1,792 CRC patients with cancer-associated VTE. In competing-risk multivariate analysis, independent predictors of recurrent VTE included age (HR with 95%CI: 1.005 [1.002-1.008] per year), history of VTE (4.288 [2.902-6.334]), index pulmonary embolism (PE) (1.698 [1.252-2.303]), ECOG ≥ 2 (1.561 [1.036-2.350]), hemoglobin < 100 g/L (1.363 [1.045-1.778]), and aPTT > 36.5 s (2.034 [1.223-3.383]); whereas recent major surgery or trauma within 1 month (0.451 [0.259-0.786]) and tumor stage II (0.607 [0.377-0.978]) or III (0.562 [0.333-0.949]) were associated with lower recurrence risk. Independent predictors of MB included age ≥ 75 (1.637 [1.011-2.652]), history of MB (5.320 [1.880-15.050]), ECOG ≥ 2 (9.979 [4.292-23.203]), antiplatelet therapy (2.592 [1.539-4.367]), and platelet count < 100×109/L (2.685 [1.336-5.397]); whereas tumor stage III (0.122 [0.053-0.278]) and metastatic cancer (0.190 [0.086-0.421]) predicted lower bleeding risk. Similarly, independent predictors of CRNMB included age ≥ 75 (1.465 [1.005-2.137]), ECOG ≥ 2 (1.750 [1.184-2.586]), hemoglobin < 100 g/L (1.870 [1.316-2.657]), and platelet count < 100×109/L (2.057 [1.076-3.932]). Recurrent VTE, MB, and CRNMB each adversely impacted one-year survival.ConclusionsThe independent risk factors identified in this study may serve as a reference for improving risk stratification in CRC patients receiving anticoagulant treatment. Additionally, adverse outcomes such as VTE recurrence, MB, and CRNMB significantly increase the one-year all-cause mortality risk in CRC patients.